Military Literature in the Medieval Roman World and Beyond
1 online resource (496 pages)
Keywords: What do the mysterious Roman author Vegetius, the Byzantine emperor Leo VI, and the Chinese general Li Jing all have in common? They are three of the dozens of authors across the medieval Mediterranean world and beyond who wrote works of military literature, sometimes called military handbooks, manuals, or treatises. This book brings together a multidisciplinary international team of scholars who present cutting edge essays on diverse aspects of medieval military literature. While some chapters offer novel approaches to familiar authors like Vegetius, and some present research on under-valued topics like Byzantine military illustrations, others provide holistic studies on subjects like early modern treatises, they all move the discussion of medieval military literature forward. Contributors are Michael B. Charles, Georgios Chatzelis, Pierre Cosme, Maxime Emion, Immacolata Eramo, Michael Fulton, David Graff, John Haldon, Catherine Hof, John Hosler, Łukasz Różycki, Katharina Schoneveld, Savvas Kyriakidis, Georgios Theotokis, Conor Whately, Michael Whitby, and Nadya Williams.